Marital disruption and economic well-being: a comparative analysis - Arnstein Aassve; Gianni Betti; Stefano Mazzuco; Letizia Mencarini (University of Essex, Institute for Social and Economic Research (ISER), 2006)
Though there is a considerable literature concerned with the economic consequences of marital breakdown, there is still substantial disagreement in terms of its magnitude. One of the major problems underlying this debate is how economic well-being is defined. In this work we implement several measures of well-being of monetary and multidimensional nature using data from European Community Household Panel. Another issue in this literature concerns selection bias of divorcing couples. We tackle this issue using a propensity score matching technique combined with a Difference-in-Differences estimator. Results confirm the importance of well-being definition. We find a high gender bias when using monetary measures but a considerably lower one or even non existent when using non-monetary indices.
Keywords: 330